2007
DOI: 10.1190/1.2757624
|View full text |Cite
|
Sign up to set email alerts
|

Elastic moduli of anisotropic clay

Abstract: Clay minerals are important components in shales, controlling their elastic properties and anisotropy. The elasticity of crystalline clay minerals differs significantly from that of clay in situ because of the ability of clay particles to bind water. In the ma-jority of published works, only isotropic moduli for in situ clays are reported. However, anisotropy is inherent in the clay elas-ticity. We develop an inversion technique for determination of the stiffness tensor of in situ clay from the shale’s stiffne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 32 publications
4
43
0
3
Order By: Relevance
“…Elastic properties of shales have been of long-standing interest (e.g., Rundle and Schuler, 1981;Hornby et al, 1994;Sayers, 1994;Jakobsen et al, 2000;Draege et al, 2006;Bayuk et al, 2007). Vasin et al (2013) propose two models based on quantitative information about mineral composition, microstructure, and preferred orientations that could be used to describe experimentally measured elastic coefficients of Kimmeridge Shale (Hornby, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Elastic properties of shales have been of long-standing interest (e.g., Rundle and Schuler, 1981;Hornby et al, 1994;Sayers, 1994;Jakobsen et al, 2000;Draege et al, 2006;Bayuk et al, 2007). Vasin et al (2013) propose two models based on quantitative information about mineral composition, microstructure, and preferred orientations that could be used to describe experimentally measured elastic coefficients of Kimmeridge Shale (Hornby, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Using this model in combination with the SCA approach, Ulm and Abousleiman (2006) estimate elastic moduli of clay minerals from measurements of elastic properties of a number of shales. Bayuk et al (2007) use the general singular approximation effective media approach to estimate the elasticity tensor of clay minerals from experimentally measured elastic properties of the Greenhorn Shale used in Hornby's study (Hornby et al, 1994). The approach of Ulm and Abousleiman (2006) and Bayuk et al (2007) is further refined by Pervukhina et al (2008aPervukhina et al ( , 2008b, who suggested using a differential effective media approach as the most relevant for shale microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Recall that all inclusions must have the same orientation and aspect ratio, and are chaotically distributed within the rock volume. Following Bayuk & Chesnokov (1998, 2007, 2008), we choose our comparison body to be a linear combination of matrix ( m ) and inclusion ( i ) properties, that is, …”
Section: Results Of Modellingmentioning
confidence: 99%